Сhemiluminescent display - Jaguiro, P.; Stsiapanau, A.; Smirnov, A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2010)
Investigation of organic liquid phase electroluminescence (traditionally, the so-called “electro-chemiluminescence” or “electrogenerated chemiluminescence”) is of special interest as a competitor for “liquid” and “solid” organic light emitted diodes (OLEDs). From the electrochemical point of view, chemiluminescence is a selfregenerating process providing high brightness light radiation due to recombination of oppositely charged dye radicals. Chemiluminescent displays have a competitive set of parameters: high light efficiency, low power consumption, low driving voltages, fast response time, high spatial resolution, very high optical transmission and wide operation temperature range. No polarizers or alignment layers are required. Samples of chemiluminescent displays, including matrix microdisplays and micromechanically made cells are available; its design and parameters are discussed in details. Theoretical and experimental investigations of thin film DC chemiluminescence phenomena are carried out. On the basis of obtained experimental results, the most important physical processes have been investigated: charge injection into solution and charge transfer by electrohydrodynamic flows. Further prospects of chemiluminescent display devices are discussed.